1994
DOI: 10.1093/brain/117.4.729
|View full text |Cite
|
Sign up to set email alerts
|

Right hemisphere restitution of language and memory functions in right hemisphere language-dominant patients with left temporal lobe epilepsy

Abstract: Concomitant with the right hemispheric restitution of language functions after early left hemisphere lesions, suppression effects on originally right hemispheric visuospatial/constructional functions have repeatedly been reported. The present study evaluated this issue in 10 right hemisphere language-dominant patients with temporal lobe epilepsy. Left hemisphere language-dominant patients with left (n = 10) or right (n = 10) temporal lobe epilepsy served as controls. The following results were obtained: in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 0 publications
7
42
1
1
Order By: Relevance
“…However, in contrast to previous studies on the crowding phenomenon (Saykin et al, 1989;Strauss et al, 1990;Carlsson et al, 1994;Helmstaedter et al, 1994;Mariotti et al, 1998;Staudt et al, 2002), no negative behavioral consequences could be ascertained in our subjects. Most importantly, we did not find major discrepancies between verbal and nonverbal performance.…”
Section: Neuropsychologic Implicationscontrasting
confidence: 99%
“…However, in contrast to previous studies on the crowding phenomenon (Saykin et al, 1989;Strauss et al, 1990;Carlsson et al, 1994;Helmstaedter et al, 1994;Mariotti et al, 1998;Staudt et al, 2002), no negative behavioral consequences could be ascertained in our subjects. Most importantly, we did not find major discrepancies between verbal and nonverbal performance.…”
Section: Neuropsychologic Implicationscontrasting
confidence: 99%
“…42,44,48 However, left and right mesial structures appear to provide highly redundant and compensatory functions in verbal memory processing. 17 Accordingly, it can be observed that nonverbal memory may be sacrificed in favor of verbal memory 20 and that material-specific impairments in TLE are less likely in the presence of generally reduced mental capacities. 19 In the surgery group, verbal memory was found to deteriorate significantly in 6 of 8 patients with left temporal resection and in 2 of 3 with right temporal resection.…”
Section: Discussionmentioning
confidence: 99%
“…Because so little is understood about the mechanisms responsible for inter-versus intrahemispheric language transfer after LH focal lesions [de Bode, 1998;Duchowny et al, 1996;Helmstaedter et al, 1994], studies of focal damage in children may not be adequate for determining the potential of the RH to serve as the substrate for the acquisition of grammar. It is often unknown whether impaired performance in these cases reflects the best efforts of the damaged LH, the linguistic performance of the RH or some combination of both.…”
Section: Literature Reviewmentioning
confidence: 99%